Household Firewood Consumption in Sweden during the Nineteenth Century - Lindmark, Magnus; Andersson, Lars Fredrik (Umeå University Library, 2011)
Household firewood consumption underwent significant changes during the industrial breakthrough. Recent literature on Sweden makes the case that greater energy efficiency drastically reduced rural household fuel consumption, while coal substituted for firewood in cities. This article shows that although coal substituted for wood in some urban areas, rural firewood consumption was not reduced. Higher standards of living indicate contrary to previous results that fuel consumption increased during the industrialisation process. The study shows that households with higher standard of living consumed more fuel and that rural households, due to lower fuel prices, consumed relatively more fuel than urban households. The result shows contrary to previous research that the total energy intensity decreased more rapidly after and not before the industrial breakthrough.